Optimization of Dikmas Lantas in Minimizing Traffic Accidents at Batang Police - Muhammad Jogi Rust Natama (Akademi Kepolisian Republik Indonesia, 2023)
Traffic accidents can happen anywhere and anytime. This study aims to describe the implementation and Organizational resources of Dikmas Lantas, Kamsel Unit in minimizing traffic accidents at the Batang Police. In conducting an analysis of implementation, researchers used POAC management theory consisting of Planning, organizing, implementing, and Controlling. Meanwhile, to describe Organizational resources, researchers used 4 aspects of assessment, namely people, Money, Materials, and Methods. The concept of optimization referred to here is how to make the steps taken by the Kamsel Unit of the Batang Police can reduce the number of accidents in the jurisdiction of the Batang Police. In addition, researchers also use the SWOT theory to identify problems internally and externally. This type of research is field research with a qualitative approach with data collection techniques in the form of interviews, document studies, and observations focused on the Batang Police jurisdiction, Central Java, which has traffic accident cases during January-November 2022. Based on the analysis that has been carried out , it is known that in discussing the implementation of Dikmas Lantas, Kamsel Unit, at the Planning stage many activities were carried out spontaneously without careful Planning, besides that in terms of Organization the number of personnel they had was still lacking. During the Dikmas Lantas, Kamsel Unit implementation stage, it seemed that what was important was just running without clear targets or goals. For the control stage, it is carried out with monthly meetings and LHP reporting, but the writing of the LHP that is made is not in accordance with Perkap No 1/2019. Regarding the management of Organizational resources managed by Dikmas Lantas the quantity of personnel is still not ideal, then in terms of the budget when compared to demands and targets it is relatively limited, the Methods used are quite varied apart from conducting direct guidance to the community, Dikmas Lantas also puts up banners and billboards in accident-prone areas.